Taking sides : - McKenna, George (McGraw-Hill/Dushkin ( A division of the McGraw-Hill companies ), 2004)
The book include 4 part: Part1: Democracy and the American political process; Part 2: The institutions of government; Part 3: Social change and public policy; Part 4: America and the world